Perbandingan Morfologi Kerang Darah di Perairan Kenjeran dan Perairan Sedati [ Comparative Morphology of Blood Cockles in Kenjeran and Sedati] - Kustiawan Tri Pursetyo; Wahju Thajaningsih; Heru pramono (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Blood cockles (Anadara antiquata, Anadara granosa) and Ark clams (Trisidos tortuosa) is one type of clams that is often consumed by people in Surabaya and Sidoarjo. The study was conducted in February-April 2014. The ratio of N/P on water conditions in Sedati of 3.3 / 1 it's indicates that the sampling process is done in the rainy season which resulted in the case of stirring the sediment. On the condition of the ratio N/P is phytoplankton still able to grow optimally. While the study site in Kenjeran, Surabaya obtained ratio N/P by 5.56 / 1 this indicates the potential of phytoplankton at this location is more optimal than the region in Sedati. In morphology, clams from Kenjeran is relatively larger than the clams from Sedati.